2020
DOI: 10.17628/ecb.2020.9.125-131
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ninhydrin With N-Hydroxyurea and N-Alkoxyureas in Acetic Acid

Abstract: We have found that ninhydrin reacted with N-hydroxyurea and N-alkoxyureas in acetic acid with the predominant formation of diastereomers of 1,3a,8a-trihydroxy-1,3,3a,8a-tetrahydroindeno[1,2-d]imidazole-2,8-dione and 1-alkoxy-3a,8a-dihydroxy-1,3,3a,8atetrahydroindeno[1,2-d]imidazole-2,8-diones, respectively. with sic-orientation of 3a,8a-HO-groups. The X-ray structural analysis of 1,3aS,8aR-trihydroxy-1,3,3a,8a-tetrahydroindeno[1,2-d]imidazole-2,8-dione and 1-n-butyloxy-3aS,8aR-dihydroxy-1,3,3a,8a-tetrahydroind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…We are deeply convinced that N-hydroxyhydantoins and Nalkoxyhydantoins may bring a huge practical value in the field of pharmaceutical and medical industries as well. Our recent research in the arylglyoxals [10] has shown a completely new way to receive the N-hydroxyhydantoins [11][12][13][14] and N-alkoxyhydantoins [12][13][14][15][16][17][18][19][20][21]. We would like to continue discussing these research results in this article.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…We are deeply convinced that N-hydroxyhydantoins and Nalkoxyhydantoins may bring a huge practical value in the field of pharmaceutical and medical industries as well. Our recent research in the arylglyoxals [10] has shown a completely new way to receive the N-hydroxyhydantoins [11][12][13][14] and N-alkoxyhydantoins [12][13][14][15][16][17][18][19][20][21]. We would like to continue discussing these research results in this article.…”
Section: Introductionmentioning
confidence: 89%
“…1 H NMR spectra were recorded on a VARIAN VNMRS 400 spectrometer (400 MHz). 13 C NMR spectra were recorded ona VARIAN VNMRS 400 spectrometer (100 MHz). The solvent DMSO-d6 was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…e addition of Si +4 with P +5 results in the formation of Bronsted acid sites, which makes these molecules more selective as catalyst for specific reaction [55][56][57][58][59][60][61][62][63][64][65][66][67]. Among the various SAPOs, SAPO-34 has a good selectivity to ethylene and propylene.…”
Section: Introductionmentioning
confidence: 99%